Epididymo-orchitis caused by Histoplasma capsulatumin a Colombian patient - Botero-García,Carlos Andrés (2017)
Abstract Although histoplasmosis is generally a self-limited disease, disseminated infection can occur in patients lacking effective cell-mediated immunity, reaching virtually every organ, even the genitourinary tract in rare cases. We report a case of epididymo-orchitis in an immunocompetent 38-year-old bricklayer from the rural area of Villeta, Cundinamarca, Colombia. The patient presented with testicular pain and macroscopic scrotal changes requiring a left orchiectomy, with microbiological isolation and molecular confirmation of Histoplasma capsulatum.